2013
DOI: 10.1007/s00011-013-0643-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inflammatory cytokine profiles in plasma of patients undergoing otorhinological surgery with propofol or isoflurane anesthesia

Abstract: An inflammatory response occurred earlier in patients who received an inhaled agent compared with an intravenous anesthetic, but no differences in plasma cytokine profiles were evident between isoflurane and propofol anesthesia in patients without comorbidities undergoing minimally invasive surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
4
11
1
Order By: Relevance
“…We have previously shown that an inflammatory response occurred earlier in patients anesthetized with isoflurane than in those anesthetized with intravenous propofol [6]. Similar to our study, occupational exposure to TCE has been reported to decrease the concentrations of the anti-inflammatory IL-10, providing evidence that TCE can be immunotoxic in humans [4].…”
Section: Discussionsupporting
confidence: 79%
“…We have previously shown that an inflammatory response occurred earlier in patients anesthetized with isoflurane than in those anesthetized with intravenous propofol [6]. Similar to our study, occupational exposure to TCE has been reported to decrease the concentrations of the anti-inflammatory IL-10, providing evidence that TCE can be immunotoxic in humans [4].…”
Section: Discussionsupporting
confidence: 79%
“… Low range of quality score. [22] Brazil Otorhinological surgery. Minor 34 TIVA with propofol compared with inhaled anaesthesia with isoflurane.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [12] , [20] , [21] , [22] , [23] , [24] with 272 patients compared the use of TIVA to inhalational anesthesia and measured IL-6 at 12 to 24 hours after surgery ( Fig 2 , A ). On meta-analysis using a random effects model, TIVA was associated with a non-significant difference in IL-6 concentration (mean difference = − 1.35, 95% CI–7.02, 9.72, P = .75).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, an inflammatory response occurred earlier in patients who received isoflurane compared with propofol anesthesia. 30 Moreover, like propofol, γ-tocopherol reduces inflammation through inhibition of cyclooxygenase type 2 activity. 31 …”
Section: Discussionmentioning
confidence: 99%